Development Of Porous Sintered Alumina By A Sponge Scaffolding Method And Pore Forming Agent Using Natural Bioresources - Keokangdong, Sengphet (2010)
Porous sintered alumina was developed using a sponge scaffolding method and pore-forming agents (PFA) using natural bioresources. The polymeric sponge method used a polyurethane foam soaked in an alumina slurry prepared by mixing alumina powder and distilled water with different concentrations of alumina, i.e. 54, 57 and 63 weight percent (wt.%) alumina. The soaked sponge was then dried in an oven at 80oC. It was then sintered at 1250 °C for 3 hours. A Field Emission Scanning Electron Microscope (FE-SEM) and an optical microscope were used to observe the morphology. A compression test was also carried out to determine the mechanical property. The different alumina concentrations produced densities ranging from 0.63 to 0.31 gcm-3 with relative porosities of 78.54 to 92.60 %, water flow rate 3.00 to 3.15 cm3/s, seepage-velocity of 0.12 to 0.14 cm/s and the compressive strength 0.45 to 0.60 MPa. The microstructure showed that small and large pores were formed and these were largely interconnected. Pore-forming agents (PFA) used for the fabrication of porous ceramics were sugar cane wastes (SC) and rice husk powder (RH). After shaping and drying, the ceramic green bodies were also sintered at 1250 °C for 3 hours. The results obtained showed that when SC was added the bulk density ranged from 1.20 to 1.27gcm-3, porosity ranged from 60.86 to 65.64%, flow rate from 0.10 to 0.13 cm3/s and seepage velocity from 0.014 to 0.029 cm/s whilst the compressive strengths ranged from 1.06 to 2.05 MPa. When RH was added, the porosity and flow rate results were reduced with increasing RH. The density of the samples increased from 1.27 to1.57 gcm-3. It shows that both sugar cane wastes (SC) and rice husk (RH) are potentially capable to produce porous alumina. However, based on the results, SC was found to be a better pore-forming agent than RH.